CD4+CD25+CD127low regulatory T cells play predominant anti-tumor suppressive role in hepatitis B virus associated hepatocellular carcinoma - Sharma, Shreya; Khosla, Ritu; David, Paul; Rastogi, Archana; Vyas, Ashish; Singh, Dileep; Bhardwaj, Ankit; Sahney, Amrish; Maiwall, Rakhi; Sarin, Shiv K.; Trehanpati, Nirupma (Frontiers in Immunology, 2015)
Background:Hepatocellular carcinoma (HCC) is the second leading cause of cancer death worldwide and hepatitis B is one of the commonest causes. T regulatory cells (Tregs) are strong immunomodulators and are likely to play a major role in HCC development. HBV infection is reported to induce expansion of Tregs. We investigated the CD4+CD25+CD127-veFoxP3+ Tregs in HBV related HCC as compared to non-HBV-HCC. Patients and Methods: Whole blood Immunophenotyping was analysed by multicolor flow cytometry in patients with HBV related HCC (HBV-HCC, n=17), non-HBV-HCC (n=22; NASH =16, alcohol related=6) and chronic hepatitis B infection (CHBV; n=10).T regulatory cells and functionality was checked by in vitro suppression assays using CD4+ CD25+ CD127low T regulatory cells. Levels of serum alpha fetoprotein(AFP),expression of FoxP3, IL-10, PD-1, TGF-β and Notch in Tregs and liver explants was analyzed by flow cytometry, immuno-histochemistry and quantitative RT-PCR.Results:CD4+CD25+hi and Foxp3 expression in CD4+CD25+hiCD127low was significantly increased (P=0.04, P=0.007) in HBVHCC compared to non-HBVHCC and CHBV patients. HBVHCC also showed high IL-10and TGF-β secreting CD4+CD25+hiTregs.The PD1 expression in CD4+CD25+hi was significantly decreased in the HBVHCC than non-HBVHCC. In HBVHCC, AFP levels were significantly high (median 941, range 2-727940) than non-HBVHCC (median 13.5, range 2-18,900). In HBVHCC,patients with high AFP (range;3982-727940 ng/ml) showed positive correlation with Foxp3 expression in CD4+CD25+hi CD127low(r=0.857,p=0.014). Reduced PD1 expression in HBVHCC also had negative correlation with FOXP3 in CD4+CD25+hi CD127low(r=-0.78, p=0.04). However, AFP levels in non-HBVHCC showed negative correlation with (R=-0.67, p=0.005) with CD4+CD25+hi Tregs. Conclusions:Our results demonstrates that CD4+ CD25+hi Tregs from HBVHCC patients have decreased expression of PD-1, resulting in higher IL-10 and TGF-β secretion. Increased suppressive ability of Tregs in HBV re